Approach to the problem of choice of the adjustable harvester parameter values based on fuzzy modeling - Lyudmila Victorovna Borisova; Inna Nikolayevna Nurutdinova; Valery Petrovich Dimitrov (Advanced Engineering Research)
A problem of selecting the controlled parameter values of the combine harvester work tools is considered. Models describing the harvesting quality factor dependencies of the external agents are analyzed. The need of a new approach to modeling the technological adjustment process of the harvester in the field which takes into account the fuzzy information on the environmental factors, its approximate character, as well as an expert method of generating information, is justified. To describe the environmental factors and the performance indices, linguistic variables are introduced, their membership functions are developed, and production rules are formulated. The fuzzy inference process is illustrated by an example of selecting the beater rate speed. A knowledgebase and an inference engine that form the expert system basis are created. The use of such a system in the field allows reducing the process downtime and crop waste. A practical implementation of the developed model is the creation of the software for the automated problem solution of the technological adjustment of the harvester in the field.